White-faced storm petrels (Pelagodroma marina) near the Galapagos Islands. - Harris, M. P., de Vries, T. (1968)
BIB Now: 3623
English
Keywords: PR -- White-faced storm petrels (Pelagodroma marina) near the Galapagos Islands. -- birds, bird distribution, storm petrels -- aves, piqueros, distribución de aves, petreles